Determination of volatile organic compounds of Tagetes filifolia Lag. (Asteraceae) from Córdoba (Argentina) using HS-SPME analysis - Vázquez, Ana María (2013)
A headspace solid-phase microextraction (HS-SPME) method followed by gas chromatography-mass spectrometry (GC-MS) and gas chromatography-flame ionization detection (GC–FID) are described for the analysis of volatile compounds in Tagetes filifolia Lag. The composition of the total aerial parts of the plant (whole plant) and the inflorescences, leaves and stems were studied separately using HS-SPME. As a result, 54 compounds were determined, of which 47 were identified. The major components observed in this analysis were trans-anethole and estragole. The HS-SPME method used for the analysis of volatile compounds of T. filifolia is simple, fast, effective, free from the use of solvents, and permits by an analysis of small amounts of samples to achieve better results in terms of the determination of the composition than those reported in the literature for the analysis of essential oil.